African Swine Fever Virus Induces STAT1 and STAT2 Degradation to Counteract IFN-I Signaling - Riera, Elena; Pérez-Núñez, Daniel; García-Belmonte, Raquel; Miorin, Lisa; García-Sastre, Adolfo; Revilla, Yolanda (Frontiers in Microbiology, 2021)
African swine fever virus (ASFV) causes a serious disease in domestic pigs and wild boars and is currently expanding worldwide. No safe and efficacious vaccines against ASFV are available, which threats the swine industry worldwide. African swine fever virus (ASFV) is a complex dsDNA virus that displays multiple mechanisms to counteract the host innate immune response, whose efficacy might determine the different degrees of virulence displayed by attenuated and virulent ASFV strains. Here we report that infection with both virulent Arm/07/CBM/c2 and attenuated NH/P68 strains prevents interferon-stimulated gene (ISG) expression in interferon (IFN)-treated cells by counteracting the JAK/STAT pathway. This inhibition results in an impaired nuclear translocation of the interferon-stimulated gene factor 3 (ISGF3) complex, as well as in the proteasome-dependent STAT2 degradation and caspase 3-dependent STAT1 cleavage. The existence of two independent mechanisms of control of the JAK/STAT pathway, suggests the importance of preventing this pathway for successful viral replication. As ASFV virulence is likely associated with the efficacy of the IFN signaling inhibitory mechanisms, a better understanding of these IFN antagonistic properties may lead to new strategies to control this devastating pig disease.